Variation in the physical activity environment according to area‐level socio‐economic position—A systematic review. (9th January 2019) - Jacobs, Jane; Alston, Laura; Needham, Cindy; Backholer, Kathryn; Strugnell, Claudia; Allender, Steven; Nichols, Melanie
Summary: Physical inactivity is a major contributing factor to obesity, and both follow a socio‐economic gradient. This systematic review aims to identify whether the physical activity environment varies by socio‐economic position (SEP), which may contribute to socio‐economic patterning of physical activity behaviours, and in turn, obesity levels. Six databases were searched. Studies were included if they compared an objectively measured aspect of the physical activity environment between areas of differing SEP in a high‐income country. Two independent reviewers screened all papers. Results were classified according to the physical activity environment analysed: walkability/bikeability, green space, and recreational facilities. Fifty‐nine studies met the inclusion criteria. A greater number of positive compared with negative associations were found between SEP and green space, whereas there were marginally more negative than positive associations between SEP and walkability/bikeability and recreational facilities. A high number of mixed and null results were found across all categories. With a high number of mixed and null results, clear socio‐economic patterning in the presence of physical activity environments in high‐income countries was not evident in this systematic review. Heterogeneity across studies in the measures used for both SEP and physical activity environments may have contributed to this result.